Phylogeny and taxonomy of the Middle Eastern geckos of the genus Cyrtopodion and their selected relatives - Červenka, Jan; Kratochvíl, Lukáš; Frynta, Daniel (Zootaxa, 2008)
Representatives of the gekkonid genus Cyrtopodion and related genera form a highly diversified group of Palearctic geckos, whose taxonomy is still unstable and phylogeny little known. This study tries to improve this situation by attempting to reconstruct the phylogeny based on two molecular markers (partial sequences of mitochondrial cytochrome b and 12S rRNA genes) in the Middle Eastern species of the genus Cyrtopodion and members of the genera Agamura and Bunopus. The results support the monophyly of the species groups within the genus Cyrtopodion as defined by Anderson (1999), but relationships between these groups remain largely unresolved. The kotschyi group (= subgenus Mediodactylus) is not closely related to the rest of the genus Cyrtopodion and should be treated as an autonomous genus. Agamura persica forms a monophyletic group with agamuroides + caspium + scabrum species groups. The genus Bunopus does not seem to be closely related to this clade. We briefly discuss the implications of our findings and stress the importance of further molecular studies in Palearctic geckos.